PIBID: Uma contribuição à política de formação docente - Fernandes, Maria José da Silva [UNESP]; Mendonça, Sueli Guadelupe de Lima [UNESP] (My University, 2013)
This article aims to present a discussion on the impact of the Institutional Program of Initiation to Teaching (Pibid) on teacher formation policy from the experience of the Universidade Estadual Paulista (Unesp). The Pibid contributes effectively to the relationship between university and basic education school constituting a great advance in the politics of initial and continuing training of teachers. The challenges and the possibilities are many, requiring from its direct participants ongoing dialogue and commitment with public school.

O presente artigo tem como objetivo apresentar uma discussão sobre o impacto do Programa Institucional de Iniciação à Docência (Pibid) na política de formação de professores a partir da experiência da Universidade Estadual Paulista (Unesp). O Pibid contribui, efetivamente, com a relação entre universidade e escola da Educação Básica se constituindo em forte avanço na política de formação inicial e continuada de professores. São muitos os desafios e possibilidades, exigindo de seus participantes diretos diálogo contínuo e compromisso com a escola pública.
PIBID: A contribution to the policy of teacher education
Keywords: formação de professores; licenciatura; Pibid